Eodromyia pumilio gen. et sp. nov., a new empidoid fly from the Earliest Eocene amber of France (Diptera: Hybotidae: Tachydromiinae) - Myskowiak, J.; Garrouste, R.; Nel, A. (Zootaxa, 2018)
Eodromyia pumilio gen. et sp. nov., is described as the oldest record of the hybotid tribe Drapetini, from the Lowermost Eocene amber of Oise (France). It differs from described extant genera in the tribe, among other characters, by the complete absence of crossvein bm-cu.